Oplyst, forbedret, saliggjort: 2 salmer af H.C. Andersen. Opposition ex auditorio ved Kaj Mogensens Disputatsforsvar 9. maj 2018. Livet – det dejligste eventyr. H.C. Andersens teologi I-II - Kjærgaard, Jørgen (Dansk Teologisk Tidsskrift, 2018)
At the same time as his Fairy Tales were being published, Hans Christian Andersen was commissioned to write two hymns for the re-opening of Holmen’s Church in Copenhagen. In his dissertation, Kaj Mogensen mainly sees these hymns as presenting an image of God as Creator, independently of their actual context in the particular church service on the day of the re-opening. The article considers the content of Hans Christian Andersen’s hymns as reflecting both the contemporary baptismal ritual and the gospel for the sermon of the day in question.